Businesses along Front St., four wheel cart, people, Nome, Alaska, between 1898 and 1900 - Hester, Wilhelm, 1872-1947 (1898)
Stamped on photo: W. Hester, Seattle -Tacoma, WA. Written on photo: 22. Businesses identified: S.G. Simpson & Co. Transportation, the Nome Telephone Office, The Bohemia hotel , Royal Cafe, The Grotto, and Columbia Theater. PH Coll 318.1061 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number